2022
DOI: 10.19182/bft2021.350.a36298
|View full text |Cite
|
Sign up to set email alerts
|

Événements climatiques extrêmes et croissance radiale de Cedrus atlantica (Manetti) dans les massifs du Belezma et du Chélia (Algérie)

Abstract: Pour mieux comprendre l'impact des facteurs climatiques et l'influence de la diversité des habitats sur le dépérissement des cédraies des Aurès, une approche dendrochronologique basée sur la relation cerne-climat a été adoptée et appliquée à six stations, réparties sur deux cédraies méridionales, du Belezma et du Chélia (Atlas saharien), distantes de 60 km et impactées par différentes perturbations climatiques. Pour les deux sites étudiés, un sondage de 120 arbres a été réalisé, permettant d’extraire au total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They found that C. atlantica growth is enhanced by cool and wet conditions in spring. Tafer et al (2021) the climate-growth relationship in two southern Algerian cedar forests in the Saharan Atlas that were subjected to different climatic disturbances. C. atlantica responded differently at the two sampled sites.…”
Section: Algeriamentioning
confidence: 99%
“…They found that C. atlantica growth is enhanced by cool and wet conditions in spring. Tafer et al (2021) the climate-growth relationship in two southern Algerian cedar forests in the Saharan Atlas that were subjected to different climatic disturbances. C. atlantica responded differently at the two sampled sites.…”
Section: Algeriamentioning
confidence: 99%